The Importance of Eating Healthy and Nutritionally Balanced Food for Elementary School Children - Herlianty Herlianty; Ni Ketut Sumidawati; Trisilia Bakue (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2024)
Health and well-being are important aspects of human life. One of the key factors that affect health is diet. The food we consume directly affects our physical and mental state. This activity aims to increase elementary school children's knowledge of the importance of eating healthy and nutritionally balanced foods. Method As an alternative solution to the problems that have been identified, counselling activities are carried out on the importance of eating healthy and nutritionally balanced foods in elementary school children. The method to increase this knowledge is counselling on the importance of eating healthy and nutritionally balanced foods. The techniques used in this activity include advising on the importance of eating healthy, nutritionally balanced foods and distributing leaflets. Based on the evaluation results, there has been a significant increase in knowledge about eating healthy and nutritionally balanced foods. Education and awareness about a healthy and nutritionally balanced diet are very important. The public needs to be adequately informed about the nutritional value of food and ways to adopt a healthy diet. Thus, it is expected to improve the quality of life, reduce disease risk, and create a healthier and more productive society overall.